2021
DOI: 10.1038/s41398-021-01294-x
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of schizophrenia risk genes from GWAS results by integrating multi-omics data

Abstract: Schizophrenia (SCZ) is a polygenic disease with a heritability approaching 80%. Over 100 SCZ-related loci have so far been identified by genome-wide association studies (GWAS). However, the risk genes associated with these loci often remain unknown. We present a new risk gene predictor, rGAT-omics, that integrates multi-omics data under a Bayesian framework by combining the Hotelling and Box–Cox transformations. The Bayesian framework was constructed using gene ontology, tissue-specific protein–protein network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Further research is needed to understand how our results can be translated into clinical effective strategies with an unprecedented mechanism that targets circHomer1 rather than Glu receptors. Since there are many genes known to be associated with SCZ 100 , 101 , the possibility of other circRNAs derived from such SCZ GWAS-linked genes should be examined. Regarding the role of circHomer1 in the regulation of SCZ-GWAS genes, our lab has previously demonstrated that in vivo circRNA-specific knockdown of circHomer1 in mouse PFC, modulates the expression of numerous alternative mRNA transcripts from genes involved in synaptic plasticity and psychiatric disease, attributing an upstream role for the SCZ-GWAS differential expression.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to understand how our results can be translated into clinical effective strategies with an unprecedented mechanism that targets circHomer1 rather than Glu receptors. Since there are many genes known to be associated with SCZ 100 , 101 , the possibility of other circRNAs derived from such SCZ GWAS-linked genes should be examined. Regarding the role of circHomer1 in the regulation of SCZ-GWAS genes, our lab has previously demonstrated that in vivo circRNA-specific knockdown of circHomer1 in mouse PFC, modulates the expression of numerous alternative mRNA transcripts from genes involved in synaptic plasticity and psychiatric disease, attributing an upstream role for the SCZ-GWAS differential expression.…”
Section: Discussionmentioning
confidence: 99%
“…The papers analyzed in this review allow to state unequivocally that there are multiple alleles of genes directly related to SGAs response treatment—both those linked to pharmacokinetics, as well as genes associated with pharmacodynamics such as those involved in dopaminergic and serotonergic neurotransmitter systems. What is more, although they have not been the focus of this paper, multiple genes unrelated to traditional theories of schizophrenia genesis have also shown significant correlation with antipsychotic response [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenia is a complex neurodevelopmental disorder that is characterized by the presence of symptoms like delusions, hallucinations, disorganized speech, and negative affect ( James et al, 2018 ; NIMH, 2020 ). While the mechanistic underpinnings of schizophrenia can be genetically derived ( He et al, 2021 ) another risk factor is early life adversity, where certain environmental stressors (e.g., physical or emotional abuse, maternal infection) contribute to permeant changes in brain physiology and behavior ( Bennouna-Greene et al, 2011 ; Kraan, et al, 2015 ; Rokita et al, 2020 ; Matheson et al, 2013 ). Stress in the prenatal environment can increase one’s risk for developing psychiatric disorders including schizophrenia.…”
Section: Schizophreniamentioning
confidence: 99%